A comprehensive dataset of surface electromyography and self-perceived fatigue levels for muscle fatigue analysis - Cerqueira, S. M.; Vilas Boas, R.; Figueiredo, J.; Santos, C. P. (Sensors, 2024)
Muscle fatigue is a risk factor for injuries in athletes and workers. This brings relevance to the study of this biochemical process to allow for its identification and prevention. This paper presents a novel dataset for muscle fatigue analysis comprising surface electromyography data from upper-limbs and the subject`s self-perceived fatigue level. This dataset contains 13 h and 20 min of data from 13 participants performing a total of 12 upper-limb dynamic movements (8 uni-articular and 4 complex/compound). This dataset may contribute to the testing of new fatigue detection algorithms and analysis of the underlying mechanisms.